2019
DOI: 10.1177/1350650119867795
|View full text |Cite
|
Sign up to set email alerts
|

Design and development of a new portable test setup to study friction and wear

Abstract: In this paper, a novel portable sliding friction and wear test rig is introduced. Unlike other laboratory-based test setups, this setup can be used for both indoor and outdoor experiments. There is also no limitation on the size and type of the substrate surface that can be used for the friction and wear test in contrast to typical test rigs, which have some limitations for the size and type of substrate surface. A small six-wheel ground robot is developed to drag the sample on an arbitrary surface for a desir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…This friction model, without the correction parameter ( ) S q , is used along with the asperity-based correction factor proposed in this paper to calculate the friction coefficient of a rubber sample sliding on an asphalt track at different velocities. In order to evaluate the modified model, the theoretical results are compared with some experimental results obtained using a sliding friction test set-up designed and developed in the Center for Tire Research (CenTiRe) [46]. The input parameters for theoretical models are explained in the next section.…”
Section: Theory Of Rubber Frictionmentioning
confidence: 99%
See 1 more Smart Citation
“…This friction model, without the correction parameter ( ) S q , is used along with the asperity-based correction factor proposed in this paper to calculate the friction coefficient of a rubber sample sliding on an asphalt track at different velocities. In order to evaluate the modified model, the theoretical results are compared with some experimental results obtained using a sliding friction test set-up designed and developed in the Center for Tire Research (CenTiRe) [46]. The input parameters for theoretical models are explained in the next section.…”
Section: Theory Of Rubber Frictionmentioning
confidence: 99%
“…Then, the numerical results were compared with some experimental results obtained from a sliding friction tester. The details of the test set-up and the experimental procedure can be found elsewhere [46]. In this experiment, a small rubber block of compound B was tested on the asphalt surface with the power spectrum shown in Fig.…”
Section: Modified Friction Model: Theory and Experimentsmentioning
confidence: 99%
“…The FT designed and developed at the Centre for Tire Research (CenTiRe), a consortium of tyre and tyre-related industry members with two word-class universities (Virginia Tech and the University of Akron), belongs to this type of tester. This innovative device is an unmanned ground vehicle [67]. The robot shown in Figure 20, aims to reproduce all relevant tyre testing conditions on any surface and in both indoor and outdoor experiments.…”
Section: On Field Friction Testermentioning
confidence: 99%
“…The six-wheel small ground robot was developed to study friction and wear of a tread block sample on different surfaces and under different operating conditions. Emami et al [67] showed the results of an experimental investigation conducted on a styrene-butadiene rubber (SBR) sample sliding on an asphalt track. The experimental results were conducted outdoor on a clean asphalt track at an outside temperature of 24 • C. The SBR sample used has dimension equal to 25.4 × 25.4 mm 2 and it is loaded with a weight of about 4.5 kg which corresponds to an equivalent pressure between the sample and the road of 81 kPa.…”
Section: On Field Friction Testermentioning
confidence: 99%
See 1 more Smart Citation